THE INFLUENCE OF SOCIAL MEDIA ON ACHIEVEMENT STUDENTS AT SCHOOL - Mashoedi, Mashoedi; Wahyuni, Bandiyah Sri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore the influence of social media use on student achievement at SDN Tambelang I for the 2023/2024 academic year through qualitative approach. The focus of this research is to understand in-depth experiences, perceptions, and subjective impacts of social media on student learning and academic achievement. Qualitative research methods used to collect data through in-depth interviews, observations participatory, and content analysis of student interactions on social media. Participant The research involved high class students at SDN Tambelang I, as well as educators and parents to gain a comprehensive perspective. Research result highlighting the complexity of social media's influence on student achievement, including positive aspects such as online collaboration, as well as challenges such as focus distractions and increased free time spent on social media. Content analysis too identify trends in student behavior on social media platforms and their impact towards their learning activities. This research makes a contribution better understanding of how social media impacts processes student learning at SDN Tambelang I. The implications of these findings can be help design educational strategies that focus more on utilization positive social media and mitigating its negative impact on academic achievement student